Vestibular modulation of spatial perception - Ferre, Elisa R.; Longo, Matthew; Fiori, Federico; Haggard, Patrick (Frontiers in Human Neuroscience, 2013)
Vestibular inputs make a key contribution to the sense of one’s own spatial location. While the effects of vestibular stimulation on visuo-spatial processing in neurological patients have been extensively described, the normal contribution of vestibular inputs to spatial perception remains unclear. To address this issue, we used a line bisection task to investigate the effects of galvanic vestibular stimulation (GVS) on spatial perception, and on the transition between near and far space. Brief left-anodal and right-cathodal GVS or right-anodal and left-cathodal GVS were delivered. A sham stimulation condition was also included. Participants bisected lines of different lengths at six distances from the body using a laser pointer. Consistent with previous results, our data showed an overall shift in bisection bias from left to right as viewing distance increased. This pattern suggests leftward bias in near space, and rightward bias in far space. GVS induced strong polarity dependent effects in spatial perception, broadly consistent with those previously reported in patients: left-anodal and right-cathodal GVS induced a leftward bisection bias, while right-anodal and left-cathodal GVS reversed this effect, and produced bisection bias toward the right side of the space. Interestingly, the effects of GVS were comparable in near and far space. We speculate that vestibular-induced biases in space perception may optimize gathering of information from different parts of the environment.